Boos : An Android Application on Learning KadazanDusun for Non-Native KadazanDusun Speakers - Amelia Jati, Robert Jupit; Elvianney, Marius (2022)
Language learning using the mobile application has become a revolution for a learning platform as more people turns to smartphones and tablets. As there are numerous language learning mobile apps that have been developed, it indicates that everyone from different backgrounds and ages can now learn a new language. Hence, an Android application on learning the KadazanDusun language is introduced as a learning platform to respond to the latest technology since there is no KadazanDusun learning platform using Android technology that is provided for non-native KadazanDusun speakers. Boos was developed to help learners effectively learn the KadazanDusun language. This application would be helpful and provide practical learning to the learner.